PERLAKUAN PENERAPAN AKUNTANSI LINGKUNGAN PADA PENGELOLAAN LIMBAH DI RSUD ASY-SYIFA SUMBAWA BARAT - Muhammad Aldi; Sudrajat Martadinata (UNIVERSITAS KARIMUN, 2023)
Environmental accounting is a record of environmental costs as a company's responsibility for the environment around the company which is isolated by company waste. The purpose of this study was to determine the application and disclosure of environmental accounting in waste management at the Asy-Syifa Regional General Hospital, West Sumbawa. The type of research used in this research is descriptive qualitative research. Based on the results of research conducted, the West Sumbawa Asy-Syifa Regional General Hospital has not implemented environmental accounting as a whole. Environmental activities carried out by the West Sumbawa Asy-Syifa Regional General Hospital are waste management activities resulting from hospital operational activities. The Asy-Syifa West Sumbawa Regional General Hospital has not implemented environmental accounting in theory, but has implemented it in practice. West Sumbawa Asy-Syifa Hospital does not have a special budget for environmental costs, but the budget for these costs is recorded as a whole in the Hospital Budget Realization Report.